2019
DOI: 10.3390/su11071859
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Outcomes of Volunteer Satisfaction in Mega Sports Events

Abstract: The role of volunteers is an important factor for the sustainability of mega sports events. Key issues in the literature on sports event volunteers are volunteer satisfaction and its determinants and outcomes. Therefore, the purpose of the current study was to investigate the effects of the fulfillment of volunteers’ psychological needs and Volunteer Management Practices (VMP) on overall volunteer satisfaction, and to test their conditional effects depending on volunteer involvement. Additionally, the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 100 publications
2
32
1
4
Order By: Relevance
“…On the respondents' future volunteering intention, the study found that community contribution, skill enrichment, positive life experiences, and volunteer engagement positively influenced intention to volunteer in the future, consistent with the findings of the studies of Alfes et al (2016), Shantz et al (2014), and Gagne (2003, hence, H7, H8, H9, and H12 are supported, whereas, connection with sport, privileges in volunteering, and social enrichment did not significantly influence intention to volunteer in the future, thus, H10, H11, and H13 are not supported, in contrast, Kim et al (2019), Doherty (2009), Downward and Ralston (2006) found that personal and social development significantly influenced sport volunteers' involvement in future volunteering endeavors.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…On the respondents' future volunteering intention, the study found that community contribution, skill enrichment, positive life experiences, and volunteer engagement positively influenced intention to volunteer in the future, consistent with the findings of the studies of Alfes et al (2016), Shantz et al (2014), and Gagne (2003, hence, H7, H8, H9, and H12 are supported, whereas, connection with sport, privileges in volunteering, and social enrichment did not significantly influence intention to volunteer in the future, thus, H10, H11, and H13 are not supported, in contrast, Kim et al (2019), Doherty (2009), Downward and Ralston (2006) found that personal and social development significantly influenced sport volunteers' involvement in future volunteering endeavors.…”
Section: Discussionsupporting
confidence: 76%
“…This study found that skill enrichment, privileges of volunteering, and social enrichment positively influence volunteer engagement, comparable to the studies made by Mecbure and Selen (2020), Kim et al (2020), Graves (2019), Stukas et al (2016) and Allen and Bartle (2014), which revealed that volunteers' engagement has a relationship to their primary motivations. The significant assessment on the relationships among the variables analyzed shows that H2, H4, and H6 are supported, while community contribution, connection with sports, and positive life experiences did not significantly influence volunteer engagement; therefore, H1, H3, and H5 are not supported, although there are findings that these intrinsic motivations were predictors of volunteer engagement, such as the studies of Kim et al (2019) and Allen and Bartle (2014), they concluded that advancing intrinsic motivations may help event organizers develop a high level of volunteer engagement.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, it is possible that the balance between life and work may affect outcomes such as satisfaction, and this variable would influence younger people more than late adults and older people [56]. In the same vein, other variables could be included in future studies, due to the preliminary evidence that suggest its relevance, as emotional intelligence [57], communication practices [58], organizational pride and trust [59], volunteer management practices [60], among others.…”
Section: Discussionmentioning
confidence: 99%
“…In doing so, the research has empirically proven determinants of volunteer satisfaction such as the extent of volunteer involvement, voluntary activities, and the fulfillment of volunteers' needs. The study emphasized that volunteers' satisfaction will positively influence their intention of future volunteering [31].…”
Section: Literature Reviewmentioning
confidence: 99%